환경방사선감시기의 NaI(Tl) 검출기를 이용한 조사선량률 결정방법 - 지영용(Young-Yong Ji), 이완로(Wanno Lee), 최상도, 정근호(Kun Ho Chung), 강문자(Mun Ja Kang), 최근식(geun-sik choi) (Journal of nuclear fuel cycle and waste technology (Online), 2013)
The energy band and the G-factor method were compared to determine the exposure rate from the measured spectrum using a NaI(Tl) scintillation detector. First, G-factors of a 3"${Φ}X3$" NaI(Tl) detector mounted to a EFRD 3300, which means the environmental radiation monitor, in Korea Atomic Energy Research Institute (KAERI) were calculated for several directions of incident photons through the MCNP modeling, and the optimum G-factor applicable to that monitor was then determined by comparing the results both the energy band method and the G-factor method. The results for these spectrometric determinations were also compared with the dose rate from a HPIC radiation monitor around a EFRD 3300. The measured value at the EFRD 3300 based on a 3"${Φ}X3$" NaI(Tl) detector was $7.7μR/h$ and its difference was shown about $3μR/h$, when compared with the results from a HPIC radiation moditor. Since a HPIC is known to be able to measure cosmic rays with the relatively high energy, the difference between them was caused by cosmic rays which were not detected in a 3"${Φ}X3$" NaI(Tl) detector. NaI(Tl) 섬광검출기로 측정한 에너지 스펙트럼으로부터 공간 감마 선량률을 계산하기 위하여 에너지밴드 방법과 G-factor 방법의 결과를 비교 검토하였다. 먼저 한국원자력연구원 내 운영 중인 환경방사선감시기 EFRD 3300에 장착된 3"${Φ}X3$" NaI(Tl) 검출기의 G-factor를 MCNP 모델링을 통하여 입사 방사선의 방향에 따라 각각 구하였으며, 이로부터 계산된 선량률과 에너지밴드 방법으로 계산된 결과의 차이를 비교 검토함으로써 EFRD 3300에 적용 가능한 최적의 G-factor 값을 유도하였다. 그리고 EFRD 3300 방사선감시기가 운영되고 있는 지역 주변에 위치한 HPIC 방사선감시기의 선량률과 비교 검토를 수행하였으며, 3"${Φ}X3$" NaI(Tl) 검출기 기반의 EFRD 3300에서 $7.7μR/h$의 측정값을 얻어 약 $3μR/h$ 정도의 차이를 보였다. 일반적으로 HPIC 방사선감시기는 고에너지 우주방사선량도 측정할 수 있는 것으로 알려져 있으므로, 이 차이는 3"${Φ}X3$" NaI 계측기로 측정되지 못하는 고에너지 영역의 우주방사선에 의한 영향으로 평가할 수 있었다.